UPLAND RICE AGRONOMIC PERFORMANCE IN RESPONSE TO DIFFERENT DOSES AND SOURCES OF NITROGEN (Colloquium Agrariae. ISSN: 1809-8215, 2020)
The aim of the present study was to evaluate the response of different doses and sources of nitrogen (N) on agronomic characteristics in upland rice. The experiments were conducted in the Federal University of Lavras, during 2015/2016 and 2016/2017 crop seasons, the plots consisted of 4 lines of 3 linear meters, with spacing among rows of 35 cm and a useful plot of 4.2 m2. The experimental design was a randomized complete block design with three replications in a 4x4 factorial design. The factor N dose consisted in (0, 50 100 e 200 kg ha-1 N) and the factor N sources consisted in (ammonium nitrate, ammonium sulphate, urea and polycote), totaling 16 treatments. The characteristics evaluated were plant height, grain yield, grain chalkness, 1000 grains weight and yield. It was concluded that the addiction of N doses and different N sources did not change the agronomic performance of the upland rice crop. There is influence of the environment on the responses of plants to nitrogen application, being observed different results in different crop seasons.